Six months in: COVID-19 and its impact on oncology social work practice. Issue 3 (4th May 2021) - Zebrack, Brad; Grignon, Michael; Guan, Ting; Long, Donna; Miller, Nina; Nelson, Krista; Otis-Green, Shirley; Rayton, Makeeta; Schapmire, Tara; Wiener, Lori
Abstract: The extent to which oncology social workers (OSWs) are available and adapting to disruptions in service delivery throughout the COVID-19 pandemic is unknown. Objectives: The purpose of this report is to outline the initial impact of COVID-19 on oncology social work practice during the first six months of the pandemic. Methods: As part of a nationwide investigation of workforce conditions for OSWs, three professional organizations surveyed their members to assess the effects of COVID-19 on changes to work hours, employment status, work setting, pay, and mode for patient contact (e.g., telephone or videoconference). Findings: Among 939 OSWs, 20% reported a reduction in work hours, and two-thirds indicated a temporary shift in work to home, with most patient contact occurring primarily via telephone or videoconference. Implications: Results speak to the essential nature of oncology social work and the need for evidence to inform OSW training and advocacy efforts for however long the pandemic continues.